PENGARUH MOTIVASI, PERILAKU DAN PEMAHAMAN TERHADAP KEPUTUSAN MASYARAKAT DALAM MEMILIH BANK SYARIAH DI ACEH TAMIANG - febi febi; Muhammad Iqbal; Abdul Hamid; Mastura (FEBI IAIN Langsa, 2019)
This study aims to look at the inﬂ uence of motivation, behavior and understanding of community decisions in choosing islamic banking, this study uses non-probability sampling technique through purposive sampling method with a sample of 84 people, not all populations can be sampled with certain considerations. the results of this study that motivation has a positive and signiﬁ cant effect on people’s decisions in choosing Islamic banks, behavior has a positive and signiﬁ cant effect on people’s decisions in choosing Islamic banks and understanding has a positive and signiﬁ cant effect on people’s decisions in choosing Islamic banks both partially and simultaneously. Based on the coefﬁ cient of determination, it can be concluded that motivation, behavior, and understanding inﬂ uence community decisions by 0.471 or 47.1%, while the remaining 52.9% is inﬂ uenced by other variables not included in this study.